Landiolol for rate control management of atrial fibrillation in patients with cardiac dysfunction - von Haehling, Stephan; Bělohlávek, Jan; Er, Fikret; Gassanov, Natig; Guarracino, Fabio; Bouvet, Olivier (European heart journal supplements, 2018)
Atrial fibrillation (AFib) is frequently associated with heart failure. Guidelines for AFib management have been recently updated and include an algorithm for acute heart rate control based on left ventricular ejection fraction and haemodynamics. Landiolol is an injectable ultra-short beta-blocker with very high beta-1 selectivity, listed in Japanese Guidelines for AFib management as potential option for rate control of patient with heart failure. Landiolol is now available in Europe with indication of controlling heart rate in AFib and supraventricular tachycardia. This review discusses existing clinical data in Japan and perspectives of landiolol use for acute rate control of AFib patients with cardiac dysfunction.
Keywords: Landiolol; Supraventricular tachycardia; Atrial fibrillation; Beta-blockers; Heart failure